The Fraud Rules in the Letter of Credit under Jordanian Legal System - Emad Mohammad Al Amaren; Che Thalbi Bt Md. Ismail; Mohd Zakhiri bin Md. Nor (Sriwijaya Law Review, 2021)
Letter of credit (L/C) has a massive role in expanding international trade operations. It is considered the most secure and stable banking service to finance foreign trade operations such as import and export. As an international contract, potential legal issues arise due to fraud practices. In this case, L/C users have to be aware of different approaches followed by domestic courts while dealing with fraud at the international level. This paper aims to identify the fraud means under the fraud rule governing L/C and its impact on Jordan's practice. By applying a qualitative and doctrinal legal approach, this paper analyses the lack of organization of the uniform customs and practice for the letter of credit (UCP No. 600). It also examines, via interviews with Jordanian judges, the perceptions of the Jordanian courts' policy regarding the fraud rule exception in L/C. The finding reveals that to protect the interests of all parties in a letter of credit transaction, Jordanian courts should extend the scope of fraud to cover sale contracts fraud in cases where bona fide holder is involved and when a confirming bank is absent, or when the credit amount has not been paid yet by the issuing bank. In respect of the bank practices, such special provisions implemented to commercial code must be issued due to the lack of legal provisions of the L/C in Jordan legislation.